2014
DOI: 10.1177/2325967114551528
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Repair With or Without Meniscal Transplantation and Osteotomy for Lateral Compartment Chondral Defects of the Knee

Abstract: Background:Treatment decision making for chondral defects in the knee is multifactorial. Articular cartilage pathology, malalignment, and meniscal deficiency must all be addressed to optimize surgical outcomes.Purpose:To determine whether significant clinical improvements in validated clinical outcome scores are observed at minimum 2-year follow-up after articular cartilage repair of focal articular cartilage defects of the lateral compartment of the knee with or without concurrent distal femoral osteotomy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 28 publications
3
20
1
2
Order By: Relevance
“…Placement of the new tibial plateau and femoral condyle allografts with meniscus will correct a few degrees of malalignment. 8,9 However, it is critical to assess the alignment after the fresh grafts are placed to determine the need for osteotomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Placement of the new tibial plateau and femoral condyle allografts with meniscus will correct a few degrees of malalignment. 8,9 However, it is critical to assess the alignment after the fresh grafts are placed to determine the need for osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Most advocate either a staged osteotomy before the transplant or a simulta-neous osteotomy concomitant with the transplant. 4,[8][9][10][11] Waiting until after the transplant to perform a staged osteotomy puts the fresh osteoarticular allografts at a risk of damage from overloading prior to the osteotomy. 12 We prefer to perform simultaneous transplant and osteotomy to prevent our patients from having to go through two separate procedures, each requiring a period of TTWB following surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 The biomechanical data suggesting the efficacy of combined malalignment correction concomitantly with meniscal and cartilage restoration has been corroborated with clinical studies (Table 3). [1][2][3][4][23][24][25][26][27][28][29][30] It is difficult to compare knee restorative procedure success between the neutralaligned patient and the patient with malalignment because of the increased complexity of knee pathology with the inclusion of malalignment. However, clinical studies suggest that combined osteotomy with meniscal transplantation or comparable clinical outcomes at 2 years as compared with isolated cartilage procedures.…”
Section: Discussionmentioning
confidence: 99%
“…cartilage restoration (microfracture, ACI, osteochondral allograft, or osteochondral autograft) can lead to comparable results with those achieved for isolated MAT or cartilage restoration. [23][24][25][26][28][29][30]36 Kazi et al 23 recently reported the largest series to-date of MAT with concomitant osteotomy. The authors found that there was comparable survival for MAT combined with osteotomy, when malalignment was present, as compared with isolated MAT in the neutralaligned cohort.…”
mentioning
confidence: 99%